Effects of Shellfish and Macro-Algae IMTA in North China on the Environment, Inorganic Carbon System, Organic Carbon System, and Sea–Air CO2 Fluxes - Liu, Yi; Zhang, Jihong; Wu, Wenguang; Zhong, Yi; Li, Hongmei; Wang, Xinmeng; Yang, Jun; Zhang, Yongyu (Frontiers in Marine Science, 2022)
Shellfish and macro-algae integrated multi-trophic aquaculture (IMTA) contribute greatly to the sustainability of aquaculture. However, the effects of large-scale shellfish and macro-algae aquaculture on the functions of the ocean carbon sink are not clear. To clarify these effects, we studied the spatial and temporal changes of inorganic and organic carbon systems in seawater under different aquaculture modes (monoculture or polyculture of shellfish and macro-algae) in Sanggou Bay, together with the variation of other environmental factors. The results show that the summertime dissolved oxygen (DO) concentration in the shellfish culture zone was significantly lower than other zones (p < 0.05), with a minimum value of 7.07 ± 0.25 mg/L. The variation of pH and total alkalinity (TA) were large across different culture modes, and the seawater in the shellfish culture zone had the lowest pH and TA than the other zones. Seasonal environment and aquaculture modes significantly affected the variation of dissolved inorganic carbon (DIC), CO2 partial pressure (pCO2), dissolved organic carbon (DOC), and particulate organic carbon (POC) concentrations. The highest values of DIC, pCO2, and POC appeared in summer, and the lowest appeared in winter. For DOC concentration, the lowest value appeared in autumn. Spatially, DIC and pCO2 were highest in the shellfish culture zone and lowest in the macro-algae culture zone, DOC was highest in the macro-algae culture zone and lowest in the shellfish culture zone, and POC was lower in the shellfish culture zone and macro-algae culture zone and higher in the remaining zones. The results of sea–air CO2 fluxes showed that except for the shellfish culture zone during summertime, which released CO2 to the atmosphere, all culture zones were the sinks of atmospheric CO2 during the culture period, with the whole bay being a strong CO2 sink during autumn and winter. In summary, large-scale shellfish–macro-algae IMTA plays an important role in the local carbon cycle and contributes to mitigating ocean acidification and hypoxia.